Advances in Social and Occupational Ergonomics Proceedings of the AHFE 2018 International Conference on Social and Occupational Ergonomics, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Goossens, Richard H. M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports on cutting-edge research on social and occupational ergonomics, presenting innovative contributions to the optimization of sociotechnical management systems related to organizational, policy, and logistical issues. It discusses timely topics related to communication, crew resource management, work design, participatory design, as well as teamwork, community ergonomics, cooperative work, and warning systems, and explores new work paradigms, organizational cultures, virtual organizations, telework, and quality management. The book also describes pioneering infrastructures implemented for different purposes such as urban, health, and enterprise, and examines the changing role of automated systems, offering innovative solutions that address the needs of particular populations. Based on the AHFE 2018 International Conference on Social and Occupational Ergonomics, held in Orlando, Florida, USA on July 21-25, 2018, the book provides readers with a comprehensive overviewof the current challenges in both organizational and occupational ergonomics, highlighting key connections between them and underlining the importance of emotional factors in influencing human performance. .
Keywords: Engineering design; Employee health promotion; Business information services; Industrial Management; Psychology, Industrial; Engineering Design; Employee Health and Wellbeing; Enterprise Architecture; Industrial Management; Work and Organizational Psychology